Bahasa Inggris - Noormaya Sari (Jurnal Admmirasi, 2021)
Presently, health services should be patient oriented and patient satisfaction is an important information for the hospital in maintaining them as clients. It is expected that quality services and reasonable tariff provided by a hospital will increase patient satisfaction. This study was conducted at Sultan Imanuddin Pangkalan Bun Hospital, Central Kalimantan, applying a cross-sectional study design with total sample of 380 patients. The primary data of the study obtained by giving each of respondent prepared questionnaire. The data were collected from May 2018 to July 2018. The study showed that level of outpatient satisfaction with services as follows. Out of 380 respondents who said they were dissatisfied were 28 respondents (7,37%), less satisfied were 182 respondents (47, 89%), satisfied were 151 respondents (39,74%) and very satisfied as many as 19 respondents (5,00%). The study also showed that service quality has a correlation with outpatient satisfaction, while service tariff do not have a significant correlation with outpatient satisfaction. It is necessary to improve the quality of service continuously in order to provide quality services and patient satisfaction. Keywords: Service quality, service tariff, outpatient satisfaction